Modifikasi Es Krim Kacang Hijau untuk Balita Wasting di Wilayah Kerja Puskesmas Berangas Kabupaten Batola Kalimantan Selatan - siti masodah; Magdalena (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Wasting is a condition of acute malnutrition that can significantly affect a child's growth and development. The prevalence of wasting still reaches 10.2% according to the 2018 Basic Health Research (Riskesdas) data, and in 2023, Barito Kuala Regency has become one of the areas with the highest rates. Wasting is caused by direct factors such as inadequate food intake and infectious diseases, as well as indirect factors like food security and parenting styles. The impact of wasting not only disrupts a child's physical health but also their cognitive and social development.To address this issue, a community service team from Poltekkes Banjarmasin implemented a program providing traditional ice cream to toddlers experiencing wasting for six days, accompanied by education on balanced nutrition for parents. The intervention results showed an average weight gain of 0.21 kg among toddlers in two villages, along with an increase in the knowledge of health cadres regarding the prevention and management of stunting. This program is expected to serve as a model for tackling malnutrition in the community